Literasi informasi dalam praktek sosial - Sri Melani (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
This paper discusses how information literacy happen. And various concepts will be introduced that is helpful towards an understanding of information literacy in social practice. Focuses on how information literacy appears to be the basis of research for researchers.